Hydrogen Peroxide Might Bleach Natural Dentin by Oxidizing Phosphoprotein. (November 2018) - Jiang, T.; Guo, Y.R.; Feng, X.W.; Sa, Y.; Yang, X.; Wang, M.; Li, P.; Wang, Y.N.
Recent studies suggested that bleaching agents may whiten teeth by oxidizing the fluorescent materials, which are the proteins located in the organic-inorganic interface. Therefore, we postulated that fluorescence of dentin came from dentin phosphoprotein (DPP) and that bleaching agents might bleach dentin by oxidizing DPP. Fifty-six specimens were randomly divided into 4 groups and exposed to distilled water, hydrogen peroxide (HP), ethylenediamine tetraacetic acid disodium salt (EDTA), and acetic acid for 24 h. After measuring the organic and inorganic components, fluorescence, and color characteristics of dentin before and after exposure, we found that when DPP was removed from dentin by EDTA, fluorescent intensity declined proportionally with the reduction in Raman relative intensity, and dentin was whitened considerably, with an Δ E value 6 times higher than that of the distilled water group. On the contrary, due to the incapability of acetic acid to dissolve DPP during decalcification, fluorescent intensity values and tooth color remained nearly unchanged after exposure to acetic acid. Dentin exposed to neutral HP showed no obvious morphologic and organic/inorganic component changes except for the destruction of DPP. Similarly, dramatically decreased fluorescent intensity and lightened color were found in the HP group. Moreover, DPP solution of the HP group exhibited decreased ultraviolet absorbance, especially between 250 and 300 nm, which arose from aromatic amino acids. The results indicated that DPP was responsible for the fluorescent properties of dentin and that HP might bleach dentin by the oxidization of aromatic amino acids in DPP. These findings are of great significance in promoting our further understanding of the mechanism of tooth bleaching and the fluorescent property of normal dentin.